PROBLEMS OF EPISTEMOLOGY IN INDIAN PHILOSOPHY OF THE COLONIAL PERIOD - Корнієнко, Олександр (SWorldJournal, 2024)
The article examines the epistemological views of the famous academic Indian philosophers of the colonial period K.C. Bhattacharya and A.Ch. Mukherjee. The author conducts this analysis based on one of Mukherjee's fundamental works «Self, Thought and Real